(3JdNjU GdCbhGd aj eYQaI GdQLGds - (3GdaGQSj, GdCSJQGHGPj, eMeO Hf Ydj Hf EHQGgje, J (B1028 (3g`s ((3YdhGf Hf HTGQI GdcYHjs)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai(B...(3bO CKHJ ajg GdCSeGA Ydi JQJjH MQha GdeYLe eQGYjG GdChd Ke GdKGfj hgcPG(B...s
(3BNQgG (B:s
...(3Yf GdSjO YejO GdOjf YHO GdeWdH hGdTjN aNQ GdOjf Hf GdYdGeI MSf(B...(3Ydi eGPcQg Edj GdeTGjN bOS Gddg CQhGMge(B...s
(3Je JCdjag aj (B10 (3LeGOi GdBNQ (B988(3g`s
(3JHUQI GdYfhGf (B:s
(3JdNjU GdCbhGd aj JMbjb CMhGd GdQLGd (B((3ebOeI(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B293s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B492s
Keywords: (3GdJGQjNs